Output-Based Aid in Honduras : An OBA Facility for the Water and Sanitation Sector - Mandri-Perrott, Cledan (World Bank, Washington, DC, 2012)
Honduras has achieved a reasonable level of access to water supply and sanitation, but gaps in coverage remain, especially in rural and peri-urban areas, and service quality for those with access is often poor. To help the Government of Honduras achieve universal coverage and improve service quality, the Global Partnership on Output-Based Aid (GPOBA) is funding a project to test the viability of an innovative output-based aid mechanism for financing water and sanitation services. Housed within the Honduran Social Investment Fund, this 'OBA Facility' the first such facility funded by GPOBA aims to improve access to water and sanitation services for about 15,000 low-income households, and to increase efficiency and transparency in sector investment funding. To be eligible for funding from the OBA Facility, projects must meet specific criteria and payments are made against verifiable results.